2020
DOI: 10.1021/acs.jpca.0c07181
|View full text |Cite
|
Sign up to set email alerts
|

Guided Diffusion Monte Carlo: A Method for Studying Molecules and Ions That Display Large Amplitude Vibrational Motions

Abstract: Diffusion Monte Carlo provides an effective and efficient approach for calculating ground state properties of molecular systems based on potential energy surfaces. The approach has been shown to require increasingly large ensembles when intra- and intermolecular vibrations are weakly coupled. We recently proposed a guided variant of diffusion Monte Carlo to address these challenges for water clusters [J. Phys. Chem. A201912380638070]. In the present study, we extend this approach and apply it to more strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…9,10 Recently, we have demonstrated that we can achieve a significant reduction in the ensemble size required for a DMC simulation by introducing a guiding function that describes the dependence of the wave function on the high-frequency intramolecular motions and have applied the approach to neutral water clusters, 10,11 protonated water clusters, and CH 5 + . 12 This development has led to an order of magnitude speed-up in these calculations, which has opened the door to DMC studies of larger molecules and clusters. Even with these advances, the computational requirements for evaluating the potential will quickly limit the size of the systems that can be studied.…”
Section: ■ Introductionmentioning
confidence: 99%
“…9,10 Recently, we have demonstrated that we can achieve a significant reduction in the ensemble size required for a DMC simulation by introducing a guiding function that describes the dependence of the wave function on the high-frequency intramolecular motions and have applied the approach to neutral water clusters, 10,11 protonated water clusters, and CH 5 + . 12 This development has led to an order of magnitude speed-up in these calculations, which has opened the door to DMC studies of larger molecules and clusters. Even with these advances, the computational requirements for evaluating the potential will quickly limit the size of the systems that can be studied.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To further showcase the power of the NEO-DF-CCSD method, we calculated the relative stabilities of four protonated water tetramer isomers, treating all nine protons quantum mechanically. This application is particularly challenging because inclusion of zero-point energy contributions is known to change the relative stabilities of these isomers at the coupled cluster level. , According to the electronic energies without zero-point energy contributions at the CCSD­(T) level of theory, the relative stabilities of these isomers are Eigen < ring < cis -Zundel < trans -Zundel (black line in Figure A) .…”
mentioning
confidence: 99%
“…In the present study, we use the GSPA approach to evaluate the spectra of H 7 O 3 + , D 7 O 3 + , H 9 O 4 + , and D 9 O 4 + , as well as the excited state energies of H 3 O + . As inputs for these calculations, we use the ground state probability amplitudes that were obtained as part of a previously reported DMC study of these ions, where we used guided DMC simulations to obtain snapshots of f = Φ 0 Ψ T . In guided DMC studies, f is represented by an ensemble of localized functions, referred to as walkers, Φ 0 is the ground state wave function of the ion of interest, and Ψ T is a guiding function.…”
Section: Methodsmentioning
confidence: 99%
“…Operationally, the descendant weight is calculated using Based on this expression for d j , the expectation value of an arbitrary multiplicative operator, A can be evaluated using Monte Carlo integration, where N w is the number of walkers in the ensemble. Additional details of the implementation of the DMC calculations are provided in ref and the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation